PAŃSTWO ŚWIECKIE A WKŁAD RELIGII DO DOBRA SPOŁECZEŃSTWA - Possenti, Vittorio (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article analyzes the relationship between man and God. Religion is a primary level of the human life, and involves individuals, human groups and communities. Therefore it has a deep social impact. Present situation invites to face the always resurgent theologico-political problem, which includes the nexus between religion and politics, the role of religion in society, and basically the question whether from God’s will derive instructions for a good society. Many modern thinkers, from Machiavelli to Hobbes and Marx eliminates the religion, so the life of individual and society, seeing it as a threat to the good of society. But like any permanent problem, the theologico-political issue is present in the past and present century; it is still active and in fact emerges strongly in recent and less recent thought (J. Habermas, J. Maritain, J. Ratzinger, J. Rawls, Ch. Taylor), which rediscover the presence and role of religion in society.